The Handbook of language emergence - MacWhinney, Brian; O'Grady, William (Wiley Blackwell, 2015)
"This book explores the latest integrated theory for understanding human language. The authors focus on the ways in which the learning, processing, and structure of language emerge from a competing set of cognitive, communicative, and biological constraints. In addition, the book examine forces on widely divergent time scales, from instantaneous neurolinguistic processing to historical changes and language evolution. Key theoretical, empirical, and methodological issues are also addressed"--